Walling in and Walling out: Middle Managers' Boundary Work - Azambuja, Ricardo; Islam, Gazi; Ancelin‐Bourguignon, Annick (Journal of Management Studies, 2023)
AbstractLiterature around middle management has highlighted the importance of intra‐organizational boundaries, focusing on the in‐betweenness and fluidity of middle‐managerial roles and practices. Yet, this literature has largely focused on the crossing of largely stable, monolithic boundaries, placing less emphasis on the plurality of emerging boundaries and the ways in which they are constructed. Focusing on boundaries as the outcomes of, rather than only as constraints upon, everyday practices, we conduct an ethnographic study across multiple sites of a Brazilian audit firm, examining middle managers' construction, maintenance and adjustment of boundaries. Drawing upon ethnographic fieldnotes and 155 formal interviews, our study reveals how middle managers fluidly manipulate boundaries' visibility and permeability to achieve specific purposes, and how different configurations of these elements generate various boundary work practices, which we describe as barricade, façade, taboo and phantom boundary work. Moreover, we show the dual orientation of middle managers' boundary work – both obstructing and facilitating boundary‐crossing – demonstrating that, in contrast to prior research, both orientations can be enacted by the same actor according to his or her purposes. By doing so, we contribute to scholarship exploring agency and plasticity as the key issues linking the existing literature on middle management with that on boundary work.